Guldpiger og Teknikdrenge – køn i teknisk skole og dets konsekvenser - Malthesen, Tea; Sørensen, Rikke (Kvinder, Køn & Forskning, 2006)
The article shows how gender works as an unnoticed principle of organization at a Danish technical school. We point out how ideas of subjects studied and gender are interwoven. As a consequence of this students are given different possibilities at the technical school depending on their choice of subject and their gender mark and the way they do gender at the technical schools. These uneven possibilities can only be understood in relation to the gendered labour market.